Tracking financial flows for immunization in Honduras. (7th May 2015) - Valdés, Werner; Janusz, Cara Bess; Molina Aguilera, Ida Berenice; Mendoza, Lourdes; Díaz, Iris Yolanda; Resch, Stephen
Highlights: Financial flows for immunization services were tracked in Honduras for 2011. An adapted SHA coding system for immunization was used. The majority of the financial flows originate from domestic resources. Some financing gaps will require attention during Gavi graduation phase. Abstract: Introduction: In Honduras, until 2008, vaccine and injection supplies were financed with domestic resources. With the introduction of rotavirus vaccine in 2009 and pneumococcal conjugate in 2011, the country's Expanded Program on Immunization required an influx of resources to support not only vaccine procurement but also investments in cold chain infrastructure and programmatic strategies. This paper examines the origin, allocation, and use of resources for immunization in 2011 in Honduras, with the aim of identifying gaps in financing. Methods: An adaptation of the System of Health Accounts (2011) codes was used to specifically track resources for immunization services in Honduras for 2011. All financial flows were entered into an Excel database, and each transfer of resources was coded with a financing source and a financing agent. These coded financing sources were then distributed by provider, health care function (activity), health care provision (line item or resource input), and beneficiary (geographic, population, and antigen). All costs were calculated in 2011 United States dollars. Results: In 2011, financing for routine immunization in Honduras amounted to US$ 49.1 million, which is equal to 3.3% of the total health spending of US$ 1.49 billion and 0.29% of the GDP. Of the total financing, 64% originate from domestic sources. The other 36% is external financing, most importantly Gavi support for introducing new vaccines. This analysis identified potential financing gaps for many immunization-related activities besides procuring vaccines, such as expanding the cold chain, training, social mobilization, information systems, and research. Conclusions: The funding for Honduras' immunization program is a small share of total public spending on health. However, new vaccines recently added to the schedule with financial support from Gavi have increased the financing requirements by more than 30% in comparison to 2008. The Honduran government and its partners are developing sustainability plans to cover a financing gap that will occur when the country graduates from Gavi support in 2016. Access to lower vaccine prices will make the existing and future program, including the planned introduction of HPV vaccine to adolescent girls, more affordable.